Avaliação do efeito da adição contínua e pulsada de sal na eficiência, estabilidade operacional, recuperação de recursos e comunidade microbiana em sistemas de granulação aeróbia - Almeida, Francisca Denise Pereira (2024)
Aerobic granular sludge (AGS) is an emerging technology for the biological treatment of domestic and industrial effluents that has stood out for its efficiency in removing pollutants and its great potential for resource recovery. The dense granules, with high biological activity and excellent sedimentability, are responsible for the AGS treatment efficiency. However, the long time for flocculent biomass granulation to occur is considered an obstacle to the application of this technology. From this perspective, the present study applied the strategy of adding NaCl continuously and in saline pulses, with the purpose of investigating the influence of salt addition on granulation, performance, biopolymer production and microbiology in AGS systems, as well how to evaluate the operational stability of AGS reactors for saline effluents. The experiment consisted of the operation of three sequential batch reactors (SBR), with the Rl system as a control without adding salt, the R2 system receiving dosing in alternating pulses of 2.5 g NaCl/L and the R3 with continuous dosing of 2.5 g NaCl/L, with the operation cycle lasting a total of 360 minutes. The results obtained indicate that the addition of salt to the reactors promoted a higher concentration of volatile suspended solids and an improvement in sedimentability, compared to the Rl reactor. This highlights that osmotic pressure stimulated biomass growth, accelerated granulation and improved the physical and sedimentability characteristics of the biomass. The granulation process occurred more quickly in R2 (between 21 and 25 days), highlighting the positive effects of intermittent salt addition through alternating pulses. Furthermore, the addition of salt did not interfere with the performance of simultaneous removal of carbon, nitrogen and phosphorus in AGS systems, demonstrating the possibility of using this technology for effluents with salinity of up to 2.5 g/L of NaCl. However, phosphorus removal efficiencies were found to be low (8-23%) in the three reactors throughout the operation. The microbiological characterization showed the predominance of the Rhodobacteraceae and Rhodocyclaceae families, which are related to the production of extracellular polymeric substances (EPS) and the removal of carbon and nutrients. Finally, it was observed that the addition of salt did not influence a greater EPS production and alginate-like exopolymers (ALE), both in the reactor with continuous NaCl dosing and in the reactor with alternating saline pulses. This result possibly arises from the low concentration of salt used, also influenced by the greater consumption of EPS and ALE in periods of substrate scarcity (famine) during the operation of the systems. Therefore, this study presents significant results that contribute to a better understanding of the effect of salt in continuous or pulsed dosages as a selection pressure strategy to accelerate granulation, as well as to analyze the behavior of the LGA system for saline effluents.